Examining the Impact of Live Streaming, Affiliate Marketing, and Flash Sale Programs on Purchase Intentions in the TikTok Shop: An Empirical Study Focused on Generation Z - Novilia, Fitri; Hendrayati, Heny; Fahreza, Mohammad (Program Studi Magister Manajemen, Institut Manajemen Koperasi Indonesia, 2024)
Live streaming has become the latest strategy in marketing products as it provides consumers with a sense of experiencing direct shopping. In live streaming, sellers and buyers can interact directly through real-time video streaming. Marketing strategies involving third-party individuals, known as affiliate marketing, are engaged in marketing activities. Several e-commerce platforms utilize this approach as it brings benefits to all parties involved. Live streaming has become a popular promotional method, especially after the pandemic. Flash sales, with their attractive offers, are highly favored by consumers as they allow them to purchase high-quality products or services at significantly low prices, but within specific time and quantity constraints. The author is interested in understanding the most influential marketing strategies that impact consumer Purchase Intention in e-commerce, particularly on new platforms like TikTok Shop. The research method employed is descriptive statistics based on the results of statistical calculations using SEM-PLS, with primary data obtained from 96 respondents through a questionnaire.